Acute prior heavy strength exercise bouts improve the 20-km cycling time trial performance - Silva, R. A. S.; Silva-Júnior, F. L.; Pinheiro, F. A.; Souza, P. F. M.; Boullosa, D. A.; Pires, F. O. (The Journal of Strength and Conditioning Research, 2014)
This study verified if a prior 5 repetition maximum (5RM) strength exercise would improve the cycling performance during a 20-km cycling time trial (TT20km). After determination of the 5RM leg press exercise load, 11 trained cyclists performed a TT20km in a control condition and 10-minute after 4 sets of 5RM strength exercise bouts (potentiation condition). Oxygen uptake, blood lactate concentration, ratings of perceived exertion (RPE), and power output data were recorded during the TT20km. Cycling economy index was assessed before the TT20km, and pacing strategy was analyzed assuming a "J-shaped" power output distribution profile. Results were a 6.1% reduction (p < 0.05) in the time to complete the TT20km, a greater cycling economy (p < 0.01), and power output in the first 10% of the TT20km (i.e., trend; p = 0.06) in the potentiation condition. However, no differences were observed in pacing strategy, physiological parameters, and RPE between the conditions. These results suggest that 5RM strength exercise bouts improve the performance in a subsequent TT20km.